One Market, One Law: EU Enlargement in light of the economic theory of optimal legal areas - Dieter Schmidtchen; Alexander R. Neunzig; Hans-Jörg Schmidt-Trenz (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2001)
Drawing on a new analytical framework provided by the economic theory of optimal legal areas, this paper identifies the factors determining the optimal size of the European Union. It applies this theory to the question of how enlargement affects the welfare of the current and the new members of the European Union as well as that of the non-qualified countries. A welfare analysis reveals that enlargement can be a pareto-superior move. But, it also shows that enlargement can impose a negative externality on those countries left behind. In this case the results of a Kaldor-Hicks test are mixed. Furthermore, it is shown that the enlargement decision of the Union is unlikely to maximize overall welfare.
Keywords: D71; F15; F02; P33; K33; 330; enlargement of the European Union; approximation of law; optimal legal areas; EU-Erweiterung; Rechtsordnung; Kosten-Nutzen-Analyse; Pareto-Optimum; Rechtsangleichung; Theorie; EU-Staaten; Osteuropa